2011
DOI: 10.1242/dev.060939
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans bicd-1, homolog of theDrosophiladynein accessory factorBicaudal D, regulates the branching of PVD sensory neuron dendrites

Abstract: SUMMARYThe establishment of cell type-specific dendritic arborization patterns is a key phase in the assembly of neuronal circuitry that facilitates the integration and processing of synaptic and sensory input. Although studies in Drosophila and vertebrate systems have identified a variety of factors that regulate dendrite branch formation, the molecular mechanisms that control this process remain poorly defined. Here, we introduce the use of the Caenorhabditis elegans PVD neurons, a pair of putative nocicepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 65 publications
7
65
0
Order By: Relevance
“…Therefore, it is not surprising that mutations in major actin regulators such as WRC, Rac family of small GTPases (unpublished result, Zou W and Shen K) or TIAM-1 would perturb PVD morphology (Aguirre-Chen et al, 2011; Smith et al, 2010). Nevertheless, it is interesting to compare the loss-of-function phenotypes between the actin regulators and those of dma-1 and hpo-30 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that mutations in major actin regulators such as WRC, Rac family of small GTPases (unpublished result, Zou W and Shen K) or TIAM-1 would perturb PVD morphology (Aguirre-Chen et al, 2011; Smith et al, 2010). Nevertheless, it is interesting to compare the loss-of-function phenotypes between the actin regulators and those of dma-1 and hpo-30 .…”
Section: Discussionmentioning
confidence: 99%
“…We noted that genetic ablation of the UNC-6 receptors UNC-40/DCC and UNC-5 altered several aspects of PVD morphology (supplemental figure 1 24,26 ) including the aberrant occurrence of overlaps between flanking menorahs in the adult (Fig.2a). We used time-lapse imaging to establish that this mutant phenotype arises from a self-avoidance defect.…”
Section: Unc-6 Signaling Is Required For Dendritic Self-avoidancementioning
confidence: 90%
“…The resulting structures resemble candelabra and have hence been named menorahs (Figures 1A, 1B, and 1D; Oren-Suissa et al, 2010). PVD dendrite formation is perturbed in mutants of the vesicular transport machinery, such as myosin and dynein (Aguirre-Chen et al, 2011), demonstrating that mechanisms of dendrite patterning are conserved in PVD neurons. Other studies have implicated additional genes in the regulation of PVD morphogenesis, such as the fusogen eff-1 (Oren-Suissa et al, 2010) and transcription factors (e.g., unc-86 /BRN3a and mec-3 /Lhx-5; Smith et al, 2010, Smith et al, 2013), and suggested a role for the UNC-6/netrin pathway in PVD dendrite self-avoidance (Smith et al, 2012).…”
Section: Introductionmentioning
confidence: 99%